Clinical Significance of MiR-27a Expression in Serum Exosomes in Patients with Heart Failure - Xie, Yuetao; hang, Jinli Z; Zhang, Ning; Liu, Guang (Cellular and Molecular Biology, 2022)
To study the clinical significance of miR-27a expression in serum exosomes in patients with heart failure (HF), this study was carried out. Totally 101 chronic heart failure (CHF) patients (research group) admitted to our hospital from April 2016 to January 2019 were enrolled, and another 30 healthy subjects (control group) who underwent physical examination during the same period were selected. The difference of miR-27a expression level in serum exosomes between the two groups of subjects was compared, so as to analyze the diagnostic value of miR-27a in CHF and the relationship between miR-27a expression level and patient prognosis. The expression level of miR-27a in peripheral blood exosomes of subjects in the control group (CG) was significantly higher than that in the research group (RG) (P<0.05), while the miR-27a expression of the latter increased significantly 3 months after treatment (P<0.05). ROC analysis showed that the AUC, sensitivity, specificity, and critical level of miR-27a in the diagnosis of CHF were 0.835, 77.23%, 80.00%, and 1.060 respectively. While after 3 months of treatment, the indicators of the RG effectively improved (P<0.05). Pearson and Sparman correlation analysis revealed that there was a significant linear correlation between miR-27a and each indicator (P<0.05). K-M survival curve analysis demonstrated that the survival rate of patients with high expression of miR-27a was significantly higher than that of patients with low expression (P<0.05). The expression of mR-27a in serum exosomes is decreased in patients with HF and has important potential value in the diagnosis and prognosis of CHF.